PENGEMBANGAN BAHAN AJAR IPS AUTENTIK: STUDI VALIDASI LEMBAR KERJA PESERTA DIDIK BERBASIS LAPANGAN DI LINGKUNGAN RUSTIC MARKET PACET - Muhammad Sendi Pegriyanto; Ahmad Fian Saputra; Riska Agnes Ristanti; Khanifa Maria Qurrota A’yun; Alina Dewi Churun Aini; Nayalla Nanda Anwari; Muhammad Ilyas Marzuqi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The conventional LKPD structure that lacks contextual exploration is the background to this research to answer the demands of the Independent Curriculum Phase D. This research focuses on the development of authentic teaching materials in the form of field-based Electronic Student Worksheets (E-LKPD) by highlighting the local economic potential in the Rustic Market Pacet area. The method used is Research-Based Instructional Design (RBID) which is adjusted through the stages of curriculum analysis, prototype design, flipbook-based digital development, and quantitative descriptive evaluation using the Aiken's V index. The research findings show that this 19-page self-guided product obtained an Aiken's V index score of 0.90 from material experts and 0.92 from media experts, thus entering the